Penegakan Hukum Pidana Terhadap Kepemilikan Senjata Api Ilegal yang Disalahgunakan yang Mengakibatkan Matinya Seseorang: Criminal Law Enforcement Against Possession of Illegally Abused Firearms that Causes Someone's Death - Hasanal Mulkan; Mona Wulandari (DOKTRINA: JOURNAL OF LAW, 2022)
According to Law No. 12 of 1951 and the criminal law enforcement process against perpetrators of illegal possession of firearms according to the Emergency Law No. 12 of 1951 as well as the obstacles encountered in the enforcement of criminal law against illegal possession of firearms by the police by selecting the relevant agencies to obtain detailed information. concerning the enforcement of criminal law against illegal possession of firearms and the application of the Emergency Law No. 12 of 1951. that Law No. 12 of 1951 concerning the possession of illegal firearms has been implemented properly and the enforcement of criminal law against perpetrators of illegal possession of firearms has been carried out in accordance with the relevant regulations. Starting from the starting point of the discussion, it can be concluded that as a criminal law enforcer against the owner of a legal firearm that is misused resulting in the death of a person, it is possible to be subject to criminal charges against the perpetrators of murder in accordance with Article 338 of the Criminal Code with the threat of imprisonment for a maximum of fifteen years in prison and preventive measures to prevent the misuse of legal firearms, are in accordance with the applicable regulations for registration and use permits, conducting raids from certain parties, medical examinations for the holder of the firearms.